EFFECTS OF GEOMETRIC PARAMETERS ON ENTROPY GENERATION IN FIRE-TUBE STEAM BOILER’S HEAT EXCHANGER - OLUMUYIWA LASODE; JOSEPH OYEKALE; IDEHAI OHIJEAGBON; JOHN OLADEJI (Journal of Engineering Studies and Research)
This paper presents a parametric study on fire-tube steam boilers’ heat exchanging unit using Entropy Generation Minimization (EGM) technique. Mathematical equation that models entropy generation rate (Ṡgen), and entropy generation number (Ns), were formulated. The entropy generation number was related to the geometric features of the system. Solving the equations showed the effects of each geometric feature on both pressure drop and Ns. Correlation equation relating dimensionless fire-tube length to dimensionless tube diameter was also obtained. The obtained correlation equation is a tool to be incorporated into fire-tube steam boiler design, so as to account for entropy generation during design.